The Effect of Hydrotherapy on Gross Motor Development in Infants Aged 6–12 Months: A Quasi-Experimental Study in Posyandu Dahlia, Palembang, Indonesia - Hanik Khairun Nisa; Devi Elfita Sari (International Journal of Health and Social Behavior, 2025)
Gross motor development is an important aspect of an infant’s growth. Infants aged 6–12 months are in a golden period where physical stimulation plays a vital role in supporting coordination, balance, and muscle strength. Hydrotherapy provides an experience of free movement in water with light resistance, which can strengthen muscles and improve body control. This study aimed to determine the effect of hydrotherapy on the gross motor development of infants aged 6–12 months at Posyandu Dahlia, Palembang City. This research used a quasi-experimental design with a pretest–posttest control group involving 30 infants (15 intervention and 15 control). The intervention was conducted twice a week for four weeks in water with temperatures of 36–37°C. The Denver II instrument was used for assessment. Data were analyzed using paired t-tests and independent t-tests with a significance level of 0.05The average gross motor development score increased significantly in the intervention group from 45.2 to 60.4 (p = 0.001), while the control group showed no significant change (p = 0.094). Hydrotherapy has a significant effect on improving the gross motor development of infants aged 6–12 months. Health workers are encouraged to use this therapy as an alternative stimulation for early childhood development in community health centers.